Relationship between loyalty and cronyism, and consequences of cronyism. - Lim, Coral Boon San. (2008)
A Conceptual Model using Asian/Chinese cultural factors to justify existence of cronyism. Explains how Confucianism, power distance, and paternalism are related to loyalty and predicts negative consequences of cronyism.